ChemInform Abstract: Operationally Simple and Selective One‐Pot Synthesis of Hydroxyphenones: A Facile Access to SNARF Dyes. Issue 36 (August 2016) - Richter, Celin; Ernsting, Nikolaus P.; Mahrwald, Rainer
Abstract: Compound (VIIb) is used as precursor in the synthesis of SNARF dye (XII).